Fall leaves fall! - Hall, Zoe, 1957- (Scholastic Press, 2000)
When fall comes, two brothers enjoy catching the falling leaves, stomping on them, kicking them, jumping in piles of them, and using them to make pictures. Includes a description of how leaves change through the year.